Systematic Review and Meta-analysis of Histological Gastric Biopsy Aspects According to the Updated Sydney System in Children. Issue 1 (9th September 2021) - Kalach, Nicolas; Zrinjka, Misak; Bontems, Patrick; Kori, Michal; Homan, Matjaz; Cabral, José; Casswall, Thomas; Chong, Sonny; Cilleruelo, Maria Luz; Faraci, Simona; Megraud, Francis; Papadopoulou, Alexandra; et al.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: A descriptive and comparative study of gastric histological aspects according to the updated Sydney classification (USC), obtained from Helicobacter pylori -positive versus H pylori -negative children referred for upper gastrointestinal endoscopy. Methods: The Prisma method was used to perform a systematic review and meta-analysis. Selection criteria were based on following key words USC, H pylori, children, endoscopy, or biopsy. Publication biases were assessed according to the Newcastle-Ottawa Scale, and a meta-regression analysis was done. The study was registered on the PROSPERO platform. Results: Between 1994 and 2017, 1238 references were found; 97 studies were retained for the systematic review with a total number of 25, 867 children; 75 studies were selected for the meta-analysis concerning 5990 H pylori -infected and 17, 782 uninfected children. H pylori -positive versus H pylori -negative children, according to the USC, showed significantly higher relative risk for gastric antral and corpus chronic inflammation, presence of neutrophils, and of lymphoid follicles, and gastric mucosa atrophy, whereas, intestinal metaplasia showed a significantly higher RR only in antral biopsies. The meta-regression analysis showed that H pylori -positive versus H pylori -negative children had significantly higher risk only for corpus activity according to age, recurrent abdominal pain, and geographical area of low H pylori prevalence. Conclusions: H pylori infection in children was associated with higher relative risk for gastric antral and corpus chronic inflammation, presence of neutrophils, lymphoid follicles, and rare gastric mucosa atrophy, whereas, rare intestinal metaplasia was only significantly higher in the antral area.